AN EXPLORATION OF THE SOURCES OF HUMANISM IN ISLAMIC EDUCATION (EPISTEMOLOGICAL ANALYSIST OF UMAR BIN KHATTAB'S THOUGHT) - Muhammad Hafizh; Sarah Dina; Muhammad Rifqi Zam zami (Program Studi Pendidikan Agama Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2023)
The research problem is the incompatibility of the vision and mission of Islamic education with the problematic state of pluralism at the time of Umar bin Khattab so that it is required to adjust education to these circumstances so that how the epistemology of the source which is the basis of humanism in Islamic Education in the perspective of Umar bin Khattab is the formulation of the problem. This research was conducted using a literature study which is classified as a type of qualitative research. Primary data refers to the book Philosophy of Islamic Education A Building of Islamic Studies and secondary data refers to a number of literature related to the theme in the form of books or research. Descriptive analysis is used to analyze a number of existing data so that the research objectives in the form of uncovering and examining the sources used by Umar bin Khattab in giving birth to the humanistic concept in education at that time can be achieved with an epistemological approach. the result of this research is that the main source of Umar bin Khattab's thinking in humanism education is the Qur'an, namely in Qs. al-Ma'idah/5: 2, Qs. al-Hujurat/49: 9 and 13, Qs. Ali Imran/3: 159 and hadith. Ali Imran/3: 159 and the relevant hadith.